Age Limit for Presidential Capres/Cawapres (Legal Analysis of MKRI Decision No. 92/PUU-XXI/2023) - Majda El Muhtaj; Anisa Amelia Purba; Iwidya Risti Sinaga; Nabila Fri Cahyani; Nur Cahyu Azizah; Mikha Valdo Tambunan; Putriana Sinaga (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This study is a normative juridical research, which is a research method by examining library materials in the form of secondary data which will be analyzed qualitatively to achieve clarity regarding the decision issued by the Constitutional Court regarding the age limit of Presidential and vice presidential Candidates from the law of the Republic of Indonesia decision no. 92/PUU-XXI/2023. This research aims to analyze in depth the legal aspects related to the decision, including its relation to Law Number 7 of 2017 concerning the Election of Age Limits for Candidates for President and Vice President. The results of this in-depth analysis are expected to provide a comprehensive understanding of the legal implications of the Constitutional Court's decision in the context of the Indonesian constitutional system. Thus, this research is expected to contribute to the understanding and analysis of legal issues relevant to the Indonesian constitutional system.